Entrepreneurship Orientation Program and Its Effect on Entrepreneurial Motivation among Future Nurses - Ali, Hind; Wafaa Abd El Azeem Al-hosany; Samah Mohamed Abd Allah (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Entrepreneurship is considered one of the most important indicators of societal awareness and rationalization in society’s development policies, plans and programs. Nurse practitioners are so multidimensional, flexible, creative, and organized that make developing and operating a private practice is a natural fit for many. This study aimed to assess the effect of entrepreneurship orientation program on entrepreneurial motivation among future nurses. Quasi-experimental research design was adopted to conduct this study. The study was conducted at Suez Canal University Hospitals. The study participants were (76) nursing interns and (37) newly graduate baccalaureates nurses. Entrepreneurial motivation Questionnaire was used for data collection. Based on the participant`s responses, the results revealed that the entrepreneurship orientation program affects the entrepreneurial motivation positively. The findings provided valuable insight for higher education institutes to design their curricular in such a way that further the self- efficacy of entrepreneurial actions and positive attitude on entrepreneurship.